Carnivorous Plants - Meekiong, Kalu; Umie Naylisa, Mohamad Asmadi; Nabilah Huda, Mohd Hisham (Forest Department Sarawak, 2023)
The Heart of Borneo Initiative was launched in 2007 by three countries that share the island of Borneo - Brunei Darussalam, Indonesia, and Malaysia. The importance of the initiative is the recognition of the area as a “life support system” and committed to work together to protect it and ensure its sustainable development. The Heart of Borneo is also a hotspot for unique and endemic fauna and flora and some of them are not so well-known to the lay people. It is with this in mind that this book is published so as to increase the understanding and knowledge of these specialised flora - carnivorous plants